A Novel Borda Count based Feature Ranking and Feature Fusion Strategy to Attain Effective Climatic Features for Rice Yield Prediction (Informatica, 2021)
An attempt has been made in the agricultural field to predict the effect of climatic variability based on rice crop production and climatic features of three coastal regions of Odisha, a state of India. The novelty of this work is Borda Count based fusion strategy on the ranked features obtained from various ranking methodologies. The proposed prediction model works in three phases; in the first phase, three feature ranking approaches such as; Random Forest, Support Vector Regression-Recursive Feature Elimination (SVR-RFE) and F-Test are applied individually on the two datasets of three coastal areas and features are ranked as per their algorithm. In the second phase; Borda Count as a fusion method has been implemented on those ranked features from the above phase to obtain the top five best features. The multi quadratic activation function based Extreme Learning Machine (ELM) has been used to predict the rice crop yield using those ranked features obtained from fusion-based raking strategy and the number of varying features are obtained which gives prediction accuracy above 99% in the third phase of experimentation. Finally, the statistical paired T-test has been used to evaluate and validate the significance of the proposed fusion based ranking prediction model. This prediction model not only predicts the rice yield per hector but also able to obtain the significant or most affecting features during Rabi and Kharif seasons. From the observations made during experimentation, it has been found that; relative humidity is playing a vital role along with the minimum and maximum temperature for rice crop yield during Rabi and Kharif seasons.